Calcium Looping for CO2 Capture in Cement Plants – Pilot Scale Test. (July 2017) - Hornberger, M.; Spörl, R.; Scheffknecht, G.
Abstract: Calcium looping has been demonstrated to be a promising technology for CO2 capture in fossil fuel fired power plants due to its high energy efficiency. Synergies between the calcium looping process and cement production endorse that the calcium looping process is a highly suitable CO2 capture process for the cement industry. In this poster, first experimental results from calcium looping for cement plant application are presented. The results were obtained at a 200 kWth pilot plant operating with two interconnected circulated fluidized beds.